Changes in electrokinetic index of buccal epithelium correlated with changes in some parameters of immunity and fecal microbiocenosis - Iryna G Kyrylenko; Igor-Severyn S Flyunt; Vitaliǐ M Fil'; Walery Zukow; Igor L Popovych (Kazimierz Wielki University, 2018)
Previously we examined relationships between electrokinetic index of the buccal epithelium (EKI) and some functional and metabolic parameters of patients with chronic pyelonephritis in the phase of remission. The purpose of this study is the relationships between changes in EKI and some parameters of immunity, fecal microbiocenosis as well as urine in these same patients. Materials and Methods. Under a observations were 32 males and 10 females by age 24-76 years with chronic pyelonephritis in the phase of remission. We determined the rate of electronegative nuclei of buccal epithelium by intracellular microelectrophoresis (EKI), counted up leukocytogram and calculated its adaptation and strain indexes by IL Popovych, evaluated immune status on a set of I and II levels recommended by the WHO as well as fecal microbiocenosis, bacteriuria and leukocyturia by routine methods. After 9-11 days of balneotherapy (drinking of bioactive water Naftussya, applications of ozokerite, mineral pools) all testes repeated. Results. A number of parameters of immunity and fecal microbiocenosis have been identified, the changes of which correlate with changes in EKI. A turn-based exclusion in the multiple regression model includes changes in the Killing Index by Neutrophils of E. coli, levels in the blood of T-active and 0 Lymphocytes, rod-nuclear Neutrophils, Entropy of the Immunocytogram, Popovych's Strain Index of Leukocytogram as well as Leukocytesuria and content in feces E. coli. R=0,686; R2=0,470; Adjusted R2=0,342; F(8,3)=3,7; p=0,004. Conclusion. Caused by balneotherapy, the increase in most patients in the EKI is accompanied by favorable changes in parameters of immunity and fecal microbiocenosis, which justifies its use to assess the effectiveness of balneotherapy.